Public Interest and Privacy: the Right to Privacy in the Cover-age of Events by the Mass Media - Anatolyevna Kirillova, Elena; Vladimirovna Bogdan, Varvara; Stepanovna Ustinovich, Elena; Olegovna Pronina, Yuliya; Aleksandrovna Kovaleva, Olga; ., . (International Journal of Engineering and Technology, 2018)
The article deals with the problems related to the balance between private and public interests when covering events by the mass media. One of the most important social tasks is coordinating various interests, reaching a compromise, and ensuring social harmony and partnership. The purpose of the present study consists in analyzing the right to privacy when covering events by the mass media and identifying specifics of private and public interests. The research is based on the observation method that allowed obtaining a specific factual material. Monitoring was carried out according to the developed plan involving the allocation of specific monitoring objects and stages. The study offers the authorsâ€™ definitions of private and public interests, highlights the main features of public interest, as well as identifies the distinctive features of private and public interests. On the basis of the conducted analysis it is proposed to introduce the Concept of privacy (the right to be left alone), excluding cases where the right to privacy can be violated and where the information related to the privacy of a person can be disseminated without the consent of the person. This proposal is practical in nature and will allow the mass media to specificate the notion of the right to privacy.Â